Studi Living Hadis: Implementasi Moderasi Beragama di Tengah Masyarakat Muslim Kudus - Emiliana, Eka; Kusumaningtyas, Amelia Titik; Kurniawan, Muhammad Arif (Jurnal Studi Agama, 2024)
This article aims to describe the implementation of religious moderation in Tanjung Karang Village, which consists of various religions, ranging from Islam, Christianity, Confucianism and Buddhism. In order to avoid conflict between communities, it is necessary to realize the principle of religious moderation. Religious moderation is a concept that emphasizes mutual respect and tolerance among different religious groups. This is as stated by the Prophet Muhammad Saw in a hadith about "ummatan wasathan" that the middle is fair and Allah made Muslims a middle people. This type of research is qualitative with data collection techniques through observation, interviews, and literature studies. The results of this study show that the Islamic community living in Tanjung Karang Village builds a moderate attitude through leisurely walks, picnics, and choir activities involving youth from various religious groups. These activities are carried out without discriminating between religions so as to create harmony and good relations between religious communities. The harmony that existed among the community then made Tanjung Karang Village chosen as one of the Ministry of Religious Affairs programs as a religious moderation village.